Mitigation of Voltage Sags: A Comparative Study of D-STATCOM and DVR - Mohd Noor Salleh, Muhd Ameerussufy Hameiz; Norain Sahari; Md Nor Ramdon Baharom (Progress in Engineering Application and Technology, 2025)
This research investigates the effectiveness of two common Flexible AC Transmission System (FACTS) devices, Dynamic Voltage Restorers (DVRs) and Distribution Static Synchronous Compensators (D-STATCOMs), in mitigating voltage sags, a significant power quality issue in electrical distribution systems. The widespread adoption of nonlinear loads and the occurrence of unsymmetrical faults in real-world power systems significantly degrade power quality, leading to disruptions in voltage and current waveforms. These disturbances, including voltage sags, swells, and harmonics, necessitate effective voltage control to maintain power quality, reliability, and availability. The research utilizes a comprehensive simulation model, developed in MATLAB/Simulink, to evaluate the effectiveness of DVRs and D-STATCOMs in mitigating voltage sags under various fault conditions. The model represents a typical power distribution system, incorporating three phase source, transformers, transmission lines, and a variety of loads. The simulation includes the introduction of different fault types, such as single line-to-ground, line-to-line, double line-to-ground, and three-phase faults. The impact of varying fault resistance on the severity of the voltage sag is also investigated. A key aspect of the research is the comparative analysis of the voltage recovery performance of DVRs and D-STATCOMs. The analysis quantifies the effectiveness of each device in restoring voltage levels to acceptable limits, measured in per unit (p.u.), and considers the voltage recovery time, the peak voltage sag depth, and the rate of voltage recovery. Statistical analysis is employed to determine the significance of any performance differences between the two devices. The research findings provide valuable insights into the optimal selection and deployment of DVR and D-STATCOM technologies for enhancing power system resilience and ensuring reliable power delivery. The results contribute to a deeper understanding of voltage sag mitigation strategies in modern power distribution systems